A novel method for treatment of Class III malocclusion in growing patients - Saad A. Al-Mozany; Oyku Dalci; Mohammed Almuzian; Carmen Gonzalez; Nour E. Tarraf; M. Ali Darendeliler (SpringerOpen, 2017)
Abstract Background Management of Class III malocclusion is one of the most challenging treatments in orthodontics, and several methods have been advocated for treatment of this condition. A new treatment protocol involves the use of an alternating rapid maxillary expansion and constriction (Alt-RAMEC) protocol, in conjunction with full-time Class III elastic wear and coupled with the use of temporary anchorage devices (TADs). The aim of this study was to evaluate the dento-skeletal and profile soft tissue effects of this novel protocol in growing participants with retrognathic maxilla. Methods Fourteen growing participants (7 males and 7 females; 12.05 ± 1.09 years), who displayed Class III malocclusions with retrognathic maxilla, were recruited. Pre-treatment records were taken before commencing treatment (T1). All participants had a hybrid mini-implant-supported rapid maxillary expansion (MARME) appliance that was activated by the Alt-RAMEC protocol for 9 weeks. Full-time bone-anchored Class III elastics, delivering 400 g/side, were then used for maxillary protraction. When positive overjet was achieved, protraction was ceased and post-treatment records were taken (T2). Linear and angular cephalometric variables were blindly measured by one investigator and repeated after 1 month. An error measurement (Dahlberg's formula) study was performed to evaluate the intra-examiner reliability. A paired-sample t test (p < 0.05) was used to compare each variable from T1 to T2. Results Treatment objectives were achieved in all participants within 8.5 weeks of protraction. The maxilla significantly protracted (SNA 1.87°± 1.06°; Vert.T-A 3.29± 1.54 mm p < 0.001), while the mandibular base significantly redirected posteriorly (SNB −2.03° ± 0.85°, Vert.T-B − 3.43± 4.47 mm, p < 0.001 and p < 0.05 respectively), resulting in a significant improvement in the jaw relationship (ANB 3.95°± 0.57°, p < 0.001; Wits 5.15± 1.51 mm, p < 0.001). The Y-axis angle increased significantly (1.95° ± 1.11°, p < 0.001). The upper incisors were significantly proclined (+ 2.98°± 2.71°, p < 0.01), coupled with a significant retroclination of the lower incisors (− 3.2°± 3.4°, p < 0.05). The combined skeletal and dental effects significantly improved the overjet (5.62± 1.36 mm, p < 0.001) and the soft tissue Harmony angle (2.75° ± 1.8°, p < 0.001). Conclusions Class III elastics, combined with the Alt-RAMEC activation protocol of the MARPE appliance, is an efficient treatment method for mild/moderate Class III malocclusions. The long-term stability of these changes needs further evaluation.